2011
DOI: 10.1007/s00421-011-2087-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation: implications of the electrically evoked sensory volley

Abstract: Neuromuscular electrical stimulation (NMES) generates contractions by depolarising axons beneath the stimulating electrodes. The depolarisation of motor axons produces contractions by signals travelling from the stimulation location to the muscle (peripheral pathway), with no involvement of the central nervous system (CNS). The concomitant depolarisation of sensory axons sends a large volley into the CNS and this can contribute to contractions by signals travelling through the spinal cord (central pathway) whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
217
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(226 citation statements)
references
References 106 publications
(173 reference statements)
7
217
0
2
Order By: Relevance
“…In order to maximize the spatial recruitment during NMES, thus minimizing the extent of muscle fatigue, it has been recommended to implement different expedients during a treatment session such as progressive increase in current intensity, alteration in muscle length, and displacement of active electrodes (Maffiuletti 2010). In this cluster of articles, further approaches have been proposed to alleviate, at least in part, discomfort and other possible complications associated to the electrically evoked contractions (Botter et al 2011;Bergquist et al 2011;Gobbo et al 2011). Fig.…”
Section: Nmes Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maximize the spatial recruitment during NMES, thus minimizing the extent of muscle fatigue, it has been recommended to implement different expedients during a treatment session such as progressive increase in current intensity, alteration in muscle length, and displacement of active electrodes (Maffiuletti 2010). In this cluster of articles, further approaches have been proposed to alleviate, at least in part, discomfort and other possible complications associated to the electrically evoked contractions (Botter et al 2011;Bergquist et al 2011;Gobbo et al 2011). Fig.…”
Section: Nmes Physiologymentioning
confidence: 99%
“…These two logical steps should necessarily precede all evidence-based applications of NMES directed toward the improvement of neuromuscular function in vivo. Within each column, studies are grouped by topic area, with the name of the first author presented in square brackets Bergquist et al (2011) provided an overview of how peripheral (direct activation of motor axon branches) and central (reflexive recruitment of spinal motor neurons by the electrically evoked afferent volley) pathways contribute to electrically evoked contractions and suggested that some of the limitations of NMES (particularly discomfort and random recruitment) could be minimized by increasing the contribution through central pathways. In fact, motor unit recruitment through central pathways may be more orderly, less synchronous and more spatially diffuse throughout the muscle, than recruitment through purely peripheral pathways.…”
Section: Nmes Physiologymentioning
confidence: 99%
“…The qualitative critique of various metric methods demonstrated for example, that although individual peak plots are indeed quite meaningful, their computation time is poor in relation to the other plots. Further, the extrema plots, with an average computational time, yield at best average meaningful data.In terms of experimental design, there were several avenues for optimisation, such as quantification of the exact site to provide optimal stimulation through use of a motor pen [27] and assessing whether to stimulate the femoral nerve or quadriceps directly as they differ in terms of aspects such as comfort [28]. Moreover, the lower limb and torso could be held still during the contraction process [29] to minimise the input of residual torques from other movements of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromuscular electrical stimulation (NMES) involves the repetitive application of pulses of stimulation over a muscle belly or nerve trunk and can restore movement and reduce muscle atrophy for people who have had a spinal cord injury or stroke (Sheffler and Chae 2007;Bergquist et al 2011). NMES activates both efferent and afferent axons, resulting in muscle contractions and the transmission of an afferent volley to the central nervous system, respectively.…”
Section: Introductionmentioning
confidence: 99%